The Effect of Income Inequality on the Probability of Banking Tensions in Iran - Mohammad Abdi Seyyedkolaee; Shahryar Zaroki; Kosar Ebrahimi Kelarijani (برنامه‌ریزی و بودجه, 2022)
Banking tension is one of the major problems in developed and developing countries nowadays. Therefore, researchers and policymakers pay decisive attention to the probability of banking tension. Meanwhile, the debate over the impact of income distribution on the banking sector and the occurrence of the banking crisis has escalated, so that in recent years, it seems that income inequality can be the cause of financial crises. Accordingly, the present study has designed a stress index for the banking system of Iran's economy. To study the effect of income inequality on the probability of banking tensions in Iran, quarterly data 1999:1-2020:4 and Markov rotational model were used. The results showed that the banking system in Iran's economy had been in a state of high tension for some periods. Finally, by estimating the Probit model, it was found that with the unequal distribution of income in Iran's economy, the probability of tension in the banking sector increases. In addition, inflation and real interest rate have a positive effect, and economic growth has a negative effect, on the likelihood of banking tension.